2006
DOI: 10.1177/154405910608500301
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Destructive Immunity in the Periodontium: Part 1—Innate and Humoral Immunity and the Periodontium

Abstract: Based on the results of recent research in the field, the present paper will discuss the protective and destructive aspects of the innate vs. adaptive (humoral and cell-mediated) immunity associated with the bacterial virulent factors or antigenic determinants during periodontal pathogenesis. Attention will be focused on: (i) the Toll-like receptors (TLR), the innate immune repertoire for recognizing the unique molecular patterns of microbial components that trigger innate and adaptive immunity for effective h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 163 publications
4
80
1
1
Order By: Relevance
“…Macrophages play a central role in the innate host response in periodontitis and other chronic infections (26,27), and we previously showed that macrophages readily recognize and respond to P. gingivalis fimbriae (11,12,14). We thus investigated whether the reduction in virulence exhibited by the accessory protein-deficient strains could be attributed, at least in part, to differential interactions with macrophages.…”
Section: Differential P Gingivalis-macrophage Interactions Determinementioning
confidence: 99%
“…Macrophages play a central role in the innate host response in periodontitis and other chronic infections (26,27), and we previously showed that macrophages readily recognize and respond to P. gingivalis fimbriae (11,12,14). We thus investigated whether the reduction in virulence exhibited by the accessory protein-deficient strains could be attributed, at least in part, to differential interactions with macrophages.…”
Section: Differential P Gingivalis-macrophage Interactions Determinementioning
confidence: 99%
“…5) The gingival epithelial layer is an innate barrier against bacterial attacks, and plays a proactive role in local immune responses. 6,7) Human gingival epithelial (HGE) cells stimulated with periodontal pathogens produce PGE 2 , which further induces excessive host inflammatory responses and results in disease progression and periodontal destruction. Accumulated evidence indicates that periodontal inflammation may be stabilized by anti-inflammatory reagents such as green tea catechin (epigallocatechin gallate; EGCg).…”
mentioning
confidence: 99%
“…The study of osteoimmunology has demonstrated that host immune responses, especially T-cell immunity, play a pivotal role in regulating osteoclastogenesis and bone remodeling (26,(32)(33)(34)(35)36). The recently identified tumor necrosis factor (TNF) family molecule receptor activator of NF-B ligand (RANKL), its receptor RANK, and its natural antagonist, osteoprotegerin (OPG), have been shown to be the key regulators of bone remodeling involved in differentiation, activation, and survival of osteoclasts and osteoclast precursors (35).…”
mentioning
confidence: 99%